Study On Uniformity of Pure Iodine with Concentration 370 Mg/Ml in Dual Energy Computed Tomography Images (International Journal of Scientific Research in Science and Technology, 2024)
Objective: To analyze a uniformity of pure iodine concentration (with concentration of 370 mg/ml) in dual energy computed tomography (DECT) images. Method: To perform this study, an in-house phantom was used. The phantom has a diameter of 16 cm, a length of 5 cm, and has 5 holes with a diameter of 1.5 cm. Iodine with concentration of 370 mg/ml were positioned at each hole of the phantom. The phantom was scanned using the GE Revolution Apex (ultrafast kV switching type DECT) with voltages of 80/140 kV. The image was reconstructed and displayed as the Iodine material density (MD) map using the Gamestrone Spectral Imaging (GSI Viewer) application. To obtain the uniformity, regions of interest (ROIs) were located at the center and edges at 3, 6, 9, and 12 o’clock. Results: The measured concentration is lower than set concentration of 370 mg/ml. It was found that average measured iodine concentrations are 277.8, 311.2, 287.5, 312.6, and 303.1 mg/ml at the center and at 3, 6, 9, and 12 o’clock, respectively. The maximum value of the measured iodine concentration is at 9 o’clock, and the minimum value of the measured iodine concentration is at center position. Hence, the iodine uniformity was less than 37 mg/ml. Conclusion: Measurement of iodine uniformity on DECT images was carried out. Uniformity is below 10% of the iodine concentration value.